ADAPTIVE USE OF TABLE TENNIS IN THE PHYSICAL EDUCATION OF SCHOOLCHILDREN WITH INCLUSION (Physical Culture and Sport: Scientific Perspective, 2025)
The article is dedicated to studying the effectiveness of using elements of table tennis in the physical education system for middle school children, particularly in inclusive classrooms. The authors analyze the role of physical education in a child’s development, with particular focus on creating equal conditions for the physical development of all students, regardless of their individual characteristics. It is determined that table tennis is an effective means of developing basic physical qualities such as coordination, reaction speed, agility, endurance, and strength, and also contributes to improving cognitive functions, such as attention concentration and mental speed.The article discusses the sensitive periods of child development, particularly the age of 10-12 years, when physical activity has a significant impact on overall development. Additionally, special attention is given to the effect of physical exercises on the socialization of children with special educational needs, their development of independence, self-confidence, and social skills. The importance of creating stimulating conditions for children with disabilities is highlighted, as this enables them to integrate into the social environment and participate in various physical activities.Based on the analysis of scientific sources and practical experience, it is confirmed that table tennis has a positive effect on children's health, particularly on the cardiovascular and respiratory systems, and contributes to the development of muscle strength and motor skills. Furthermore, table tennis enhances visual perception and cognitive abilities, helping children improve their ability to react quickly and make decisions.The article also proposes methods for using table tennis in physical education, especially for children with special educational needs, such as training sessions, tournaments, game-based learning, and individual coaching. The importance of adapting educational programs according to the needs and capabilities of students is emphasized, as this fosters increased interest in sports and the development of personal qualities necessary for successful self-realization in life and sports.Thus, table tennis is an effective tool for the physical and social development of middle school children, promoting their integration into society and the development of key physical and cognitive skills.
Keywords: table tennis; adaptive physical education; schoolchildren